EFEKTIVITAS ANALGETIK EKSTRAK ETANOL AKAR ALANG-ALANG (Imperata cylindrica (L) Beauv ) PADA MENCIT PUTIH JANTAN - Kartika, Dewi; Gultom, Veronika Yuliyani; Sitompul, Andelila Suprianti (Jurnal FARMASIMED (JFM), 2020)
Pain is an unpleasant sensory and emotional experience due to tissue damage, either actual or potential or described in the form of damage. Provision of therapeutic doses of analgesics relieve pain or suppress. Plants Imperata cylindrica L. Beauv empirically used as traditional medicine. The purpose of this study to know the analgetic effect of root ethanol extract of alang-alangImperata cylindrica L. Beauv. This study was done by infra red (IR) plantar test method with a wavelength of 96 nm. Twenty male mice were divided into 4 groups. Three groups were given ethanol extract of Imperata cylindrica L. Beauv branches at a doses of 15 mg/kg bb, 30 mg/kg bb 60 mg/kg bb and one group was given 0,5% CMC Na (control) orally. After that, the time (second) hold infra red induction of pain every 10 minutes to 60 minutes. The data obtained were processed using one-way analysis of variance (ANOVA) and followed test the level of 95%. The results of phytochemical screening Imperata cylindrica L. Beauv is alkaloid, flavonoid, and steroid/triterpenoid. Ethanol extract Imperata cylindrica L. Beauv dose of 15 mg/kg bb average induction able to withstand pain of 12,86; 14,34; 15,44; 19,2; 17,52; 15,42 second, the dose of 30 mg/kg bb 13,6; 17,08; 19,82; 18,44; 16,9; 16,48 second, and a dose of 60 mg/kg bb 16,96; 18,9; 18,94; 22,14; 18,0; 17,26 second. Pain is an unpleasant sensory and emotional experience due to tissue damage, either actual or potential or described in the form of damage. Provision of therapeutic doses of analgesics relieve pain or suppress. Plants Imperata cylindrica L. Beauv empirically used as traditional medicine. The purpose of this study to know the analgetic effect of root ethanol extract of alang-alangImperata cylindrica L. Beauv. This study was done by infra red (IR) plantar test method with a wavelength of 96 nm. Twenty male mice were divided into 4 groups. Three groups were given ethanol extract of Imperata cylindrica L. Beauv branches at a doses of 15 mg/kg bb, 30 mg/kg bb 60 mg/kg bb and one group was given 0,5% CMC Na (control) orally. After that, the time (second) hold infra red induction of pain every 10 minutes to 60 minutes. The data obtained were processed using one-way analysis of variance (ANOVA) and followed test the level of 95%. The results of phytochemical screening Imperata cylindrica L. Beauv is alkaloid, flavonoid, and steroid/triterpenoid. Ethanol extract Imperata cylindrica L. Beauv dose of 15 mg/kg bb average induction able to withstand pain of 12,86; 14,34; 15,44; 19,2; 17,52; 15,42 second, the dose of 30 mg/kg bb 13,6; 17,08; 19,82; 18,44; 16,9; 16,48 second, and a dose of 60 mg/kg bb 16,96; 18,9; 18,94; 22,14; 18,0; 17,26 second.